The contribution of chronic endometritis to reproductive system disorders in patients with repeated implantation failures - Victor E. Radzinsky (IP Berlin A.V., 2021)
Chronic endometritis (CE) is a disease of continuous and invisible inflammation characterized by infiltration of plasma cells in the stromal region of the endometrium. Numerous studies have proven that CE leads to repeated implantation failures. While it is believed that the etiology of CE is mainly associated with microorganisms, the key links in pathogenesis are yet not fully understood, although there is a modern evidence that CE causes local immune disorders and impaired endometrial decidualization. Considering the insufficient effectiveness of antibiotic therapy for CE, especially in cases of resistant pathogens, or in the case of viral chronic endometritis, regimens with additional treatment that affect other etiopathogenetic pathways of CE development and maintenance are necessary. One of the methods that affects etiopathogenesis of CE is a cytokine therapy. In this review, the authors tried to consider CE with special emphasis on the etiology, epidemiology, clinical features, pathophysiology, and treatment of CE and reproductive disorders in women in association with repeated implantation failures. The review ends with a description of the clinical case.